Zwischen Bankenrettungen und autoritärem Wettbewerbsregime: Zur Dynamik des europäischen Krisenmanagements - Heinrich, Mathis (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2012)
The global financial crisis did not only plunge the European Union into a deep recession, but also released remarkable contradictions within the organisation and regulation of the European economy. As complex as the structural causes of the crisis are, the diverse and disputed are the political struggles and policy reactions to it. In particular, the different spheres of activity in European crisis management are characterised by variegated compromises, however no progressive change in European modes of regulation and underlying transnational social and political power networks seems to take place. Rather, alternative approaches are getting constantly disarticulated by discursive and organisational means, while authoritarian European policy reactions do not only deepen the crisis dynamics in Europe, but also more and more point towards a major crisis of democracy.